COVID-19 IMPACT ON MEDICAL EDUCATION OF II YEAR MBBS STUDENTS IN A TEACHING INSTITUTE – A PROSPECTIVE OBSERVATIONAL STUDY - Londhe, Vasundhara; Shinde, Vinod; Bhosale, Uma (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The coronavirus disease 2019 (COVID-19) has caused unprecedented disruption to the medical education process and to health-care systems worldwide. In India, almost medical schools have been suspended during the pandemic, and many students were staying at home to abide by social distancing guidelines. This has disrupted the medical education process and has increased the need to find alternatives. Methods: This was an observational, cross-sectional questionnaire-based online study by the Faculty of Pharmacology for Phase II Medical students of SKNMC and GH, Pune. Results: Eighty-three students responded to the online questionnaire. About 31.3% students were comfortable while using computers, mobiles, and tablets. Compare to conventional teaching method overall experience regarding the online teaching was average of 62.7%, while it was excellent for 19.3% of students and poor for 13.3%. COVID-19 also had impact on the examination of medical students (74.7%). Furthermore, students were not able to learn practical skill online (77.1%). Many students believed that this COVID-19 affected their future interest career plan while few were neutral and disagree. Conclusion: During COVID-19, virtual teaching help the students to increased their knowledge and increased their willingness to learn. Which they might find useful later on when they go back to the medical college to continue their studies. However, around one-third of students believe that the pandemic has hampered their capacity for long-term planning.